Metabolic and bone profile in postmenopausal women with and without type 2 diabetes: a cross-sectional study - Dumitru Nicoleta; Carsote Mara; Cocolos Andra; Petrova Eugenia; Olaru Maria; Caragheorgheopol Andra; Dumitrache Constantin; Ghemigian Adina (Sciendo, 2019)
Introduction. Current studies support the implication of metabolic changes associated with type 2 diabetes in altering bone metabolism, structure and resistance.